1991
DOI: 10.1002/ffj.2730060304
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic plants of tropical central Africa. V. volatile components of three zingiberaceae from Cameroon: Aframomum melegueta (roscoe) K. Schum., A. Daniellii (hook. f.) K. Schum. and A. Sulcatum (oliv. and hanb.) K. Schum.

Abstract: The essential oils isolated from the seeds of Aframomum melegueta (Roscoe) K. Schum., A. daniellii (Hook. f.) K. Schum. and A . sulcatum (Oliv. and Hanb.) K. Schum. by hydrodistillation were analysed by GLC and GC-MS. The essential oil of A. melegueta presents a characteristic composition with p-caryophyllene (8.5 %), a-humulene (31.3 %) and their epoxides (respectively 17.9 % and 27.7 %) as main constituents. With its high content of 1,8-cineole (48.9 %), the A. daniellii oil can be related to other species o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 11 publications
2
11
0
Order By: Relevance
“…melegueta was that done by our laboratoryon the seeds of a Cameroonian species (2). In this study, we found that P-caryophyllene, a -humulene and their epoxides were the main constituents (85.4% altogether).…”
Section: Previous Workmentioning
confidence: 93%
See 1 more Smart Citation
“…melegueta was that done by our laboratoryon the seeds of a Cameroonian species (2). In this study, we found that P-caryophyllene, a -humulene and their epoxides were the main constituents (85.4% altogether).…”
Section: Previous Workmentioning
confidence: 93%
“…We would like to conclude that the oils from the Central African Republic do not clearly fit into any of the categories we have previously defined for the classification ofAframomum oils (2).…”
Section: Previous Workmentioning
confidence: 97%
“…In 1991, Menut et al 1 identified nine compounds in essential oil of A. meleguata from Cameroon, in particular β-caryophyllene, α-humulene and their oxides. In 1999, Ajaiyeoba and Ekundayo 5 identified 27 compounds (98.6% of the oil) in the volatile oil from Nigerian maniguette.…”
Section: Introductionmentioning
confidence: 99%
“…The reddish-brown seeds, commonly referred to as 'alligator pepper', 'guinea grains' or 'grains of paradise', have a strong aromatic flavour and a pungent taste. 1 These seeds are widely employed as spices, and are also ingredients in numerous local medicines. Their oil appears to have antioxidant, antimicrobial and cytoprotective properties.…”
Section: Introductionmentioning
confidence: 99%
“…have been the object of numerous chemical investigations, most of them relating to their fruits. [9][10][11][12][13] Nevertheless, the volatile constituents of the leaves and rhizomes have been less investigated, although these parts of the plants are often used in food and traditional medicine. The essential oils obtained from leaves of Aframomum spp.…”
Section: Introductionmentioning
confidence: 99%